Duct tape selling : think like a marketer, sell like a superstar - Jantsch, John (New York : Portfolio, 2014)
' A new paradigm gives salespeople the tools to think and act more like successful marketers The art of selling has evolved tremendously over the last few years. Today's hectic pace demands that sales professionals rethink their strategies and practices. They must attract, teach, convert, serve, and measure while developing an individual brand that stands for trust and expertise. Now the popular author of Duct Tape Marketing teaches sales professionals how to apply the tactics of traditional marketing to their daily work. In Duct Tape Selling, salespeople will learn how to develop a marketing-based system to dramatically increase their effectiveness, stand above their competitors, and add value to their customer relationships. Jantsch flips the traditional business model-where marketers owned the message while sellers owned the relationships-on its head. These days, he argues, marketers must get better at relationships and sales must perfect the message and delivery'--
'The popular author of Duct Tape Marketing teaches sales professionals how to apply the tactics of traditional marketing to their daily work. In Duct Tape Selling, salespeople will learn how to develop a marketing-based system to dramatically increase their effectiveness, stand above their competitors, and add value to their customer relationships. Jantsch flips the traditional business model--where marketers owned the message while sellers owned the relationships--on its head. These days, he argues, marketers must get better at relationships and sales must perfect the message and delivery'--
Introduction: Changing the context of selling -- Mind-set of the new sales guide. Listen perceptively ; Connect the community ; Define leads ; Find your value proposition ; Build a reputation ; Guide the sales journey ; Teaching sells -- Practices of the new sales guide. Create an expert platform ; Become an authority ; Mine networks ; Build your sales hourglass ; Finish the sale -- The world of the new sales coach. Change the channel ; Swallow the whistle ; Bridge the gap ; Find your method ; Rethink hiring ; Manage automation -- Conclusion.
Includes index.
Keywords: Selling -- Handbooks, manuals, etc; Branding (Marketing); Customer relations